The association between observed mentor-mentee relationship quality and self-reported mentee and parent-reported externalizing behavior - Holmström, Freja, author; Haddock, Shelley, advisor; Zimmerman, Toni, committee member; Henry, Kimberly, committee member (Colorado State University. Libraries, 2020)
Youth mentoring programs can have a significant impact in the lives of at-risk youth. A relationship between youth and an adult can act as a powerful protective factor for youth at risk of developing externalizing behaviors (conduct problems and delinquency). Within the mentor dyad, the quality of the mentoring relationship is theorized to be the key mechanism of change, and there is empirical support that the quality of the mentoring relationship is associated with positive youth outcomes. Specifically, a high-quality mentoring relationship is related to a reduction in externalizing behaviors. Historically, almost all assessments of mentoring relationship quality are self-reports, thus to build upon the existing literature, this thesis incorporates the novel component of observed mentor-mentee relational quality in relation to externalizing behavior within the context of Campus Connections (CC), a time-limited and structured therapeutic mentoring program.